Geothermal potential assessment in volcanic zones through thermo-mechanical modelling a methodological proposal and international collaboration applied to Cerro Blanco (Argentina) - Likerman, Jeremias (2025)
This work presents a research proposal developed within the framework of the LincGeotermia bilateral project between Argentine and Spanish institutions. The main objective is to design a numerical methodology for evaluating geothermal potential in active volcanic zones, combining thermo-mechanical modelling, geochemical analyses, and geophysical data integration. The study focuses on the Cerro Blanco Volcanic Complex (Catamarca, Argentina), chosen as a natural prototype due to its Holocene volcanic activity, thermal surface manifestations, and available geological information. The project seeks to foster collaboration between teams with experience in geodynamic modelling, thermal subsurface characterization, and hydrothermal systems, to develop a transferable workflow applicable to other volcanic settings such as the Canary Islands. The initiative emphasizes the multidisciplinary and cooperative nature of the research, aligning with Sustainable Development Goals related to clean energy, innovation, and climate action.